State naloxone co-prescribing laws show mixed effects on overdose mortality rates. (July 2022) - Duska, MaryKate; Rhoads, Jared M.; Saunders, Elizabeth C.; Onega, Tracy
Objective: To examine the relative changes in opioid overdose mortality rates between states that have and have not adopted naloxone co-prescribing laws. Methods: We performed a synthetic control analysis. National Vital Statistics data for the years 2012–2018 were analysed, and five states with naloxone co-prescribing laws were examined: Arizona, Florida, Rhode Island, Vermont, and Virginia. Opioid overdose-related deaths were identified through cause-of-death ICD-10 codes. Results: Our pooled analysis for all opioid-related deaths showed no significant changes in opioid-related mortality rates in treated states, post naloxone co-prescribing law adoption (−0.05; 95% CI: −0.43, 0.33). Rates of other and unspecified narcotic-related mortality rates in Rhode Island were found to have decreased post-law adoption (−0.13; 95% CI: −0.25, −0.00). Conclusions: These findings suggest that naloxone co-prescribing laws were not associated with changes to overall opioid overdose mortality rates, post-law adoption, during the study period. However, Rhode Island did see a decrease in other and unspecified narcotic-related mortality rates post-law adoption. This is perhaps due to the comprehensive nature of the state's law. As overall rates of naloxone co-prescribing remain low, interventions to enhance naloxone prescribing and distribution may be necessary for co-prescribing laws to impact opioid-related mortality rates.